Meaning Reflectivity in Later Life: The Relationship Between Reflecting on Meaning in Life, Presence and Search for Meaning, and Depressive Symptoms in Older Adults Over the Age of 75 - Dewitte, Laura; Dezutter, Jessie (Frontiers in Psychology, 2021)
Background: Over the last decades, there is growing attention for the importance of meaning in life for older adults. However, there is virtually no insight into the mental processes that contribute to this experience. Some scholars recently called for an investigation of meaning reflectivity, or the process of reflecting on issues specifically related to meaning in life. In this study, we explored to what extent older adults talk and think about issues of meaning in life, and how this meaning reflectivity is related to the search for and presence of meaning in life, and to depressive symptoms. Method: In this cross-sectional observational study, 282 community-residing older adults (75 or older) in Belgium filled in paper questionnaires on meaning in life (presence and search), depressive symptoms, and meaning reflectivity (categorical item). ANOVA analyses were used to explore differences in meaning in life and depressive symptoms across the meaning reflectivity categories. Regression and negative binomial models investigated the association between meaning reflectivity and presence, search and depressive symptoms. Finally, an exploratory structural equation model examined whether presence of meaning statistically mediated the relationship between meaning reflectivity and depressive symptoms. Results: The majority of participants (42.4%) indicated that they had thought about meaning in life before, 23.2% indicated that they had talked about it before, 18% indicated that they hadn’t thought about it before but found it interesting, and 16.4% indicated that they were indifferent/unconcerned about meaning in life. The latter group reported lower levels of presence of meaning and search for meaning and higher levels of depressive symptoms. Belonging to this category was also associated with lower presence and search in regression analyses, but not with depressive symptoms above the effect of presence of meaning. Exploratory mediation analyses suggested that presence of meaning may be a mediator between meaning reflectivity and depressive symptoms. Conclusion: Meaning reflectivity is an important process to consider in the context of the experience of meaning in life for older adults. Those older adults who are indifferent about issues of meaning in life might be more vulnerable to experience a lack of meaning and depressive symptoms.